Substitusi Impor Daging melalui Sistem Kontrak Bagi Hasil Ternak - Prabowo, Rokh Eddy (Proceeding Fakultas Ekonomi, 2013)
This research is aimed at finding the significant characteristics of livestockmanagement which indicate the varieties of the profit-shared contract of livestockmanagement. It is expected that by understanding each of those characteristics, people mayoptimize the results of the management system of livestock. The study relates to cattlefattening, breeding cattle, buffaloes and goats. The research which was conducted inBoyolali, Central Java in 2000 involved 78 respondents. The data were processed byPrincipal Component Analysis (PCA), and the main factors that showed the significantvarieties of livestock management were calculated by using Discriminant Analysis. Theresults of the analyses indicate nine major components which were significant in the contractsystem, i.e.: (1) Factor 1: the aspects of agentâs net revenue and the principal share, (2) Factor2: the aspects of ratio of contract revenue, (3) Factor 3: the aspects of agentâs share, (4)Factor 4: the aspects of transaction costs, (5) Factor 5: the aspects of transport costs and timeallocation for maintenance, (6) Factor 6: the aspects of agentâs gross revenue, (7) Factor 7:the aspects of family size, (8) Factor 8: the aspects of experience in maintaining livestock, (9)Factor 9: the aspects of principal income. The results may recommend that managinglivestock with profit-shared contract should be more effective and efficient when peopleconsider the characteristics of agents in managing livestock. It is comparatively an advantagethat there are so many livestock farmers who acted as agents in Indonesia. Therefore, they arean incredible asset to produce meat in an attempt to substitute the imported meat.Keywords: contract system, livestock management, principal, agent, substitution of importedmeat